Evolution of Negligence from Classical Theory of Crime to Modern System (Dogmatic-Systemic Analysis) - Kharanauli, Levan (Journal of Law, 2018)
The article reviews specific features of development of the crime of negligence in the light of dogmatic-systemic analysis, demonstrating the nature of negligence and its place in classical, neoclassical and finalist doctrines. The paper discusses various aspects of negligence from this very view-point, with due consideration of the trends of its development.